Chapter Tracking Venice's Maritime Traffic in the First Age of Globalization: A Geospatial Analysis - Gluzman, Renard (Atti delle «Settimane di Studi» e altri Convegni, 2019)
The present collaborative work in progress is an empirical attempt verifying the interplay between political change, fleet nationality, and the evolution of shipping networks. On the basis of historical data on ship positions retracted from archival sources, we create GIS-based online maps to conduct a geospatial analysis of the traffic intensity and movement patterns along the regional and inter-regional sea routes that connected the Venetian port system with the Mediterranean ports, with special attention to the Eastern Mediterranean. In this sense, the platform "simulates" modern real-time technologies used to visualise shipping trends per vessel types.